PENYULUHAN PERLINDUNGAN HUKUM GURU DAN ADAB SISWA SEBAGAI PESERTA DIDIK TINGKAT SEKOLAH MENENGAH ATAS (SMA) - Umardani, Mohammad Kharis; Liany, Lusy (Jurnal BALIRESO, 2017)
The teacher is the person who interacts most and communicates with the students. Therefore, thefirst accused party when there is a case that affects the student is the teacher. The teacher, besidesas a teacher and educator, must also act as a parent as well as a friend to his students. So as ateacher they also need legal protection in performing professional duties. However, in thisteaching-learning process students as learners must also understand how adab in science.Community service activities are conducted by participatory action method in the form of lecturesand discussions. Based on preliminary evaluation and final evaluation, the results are significantlyimproved so that it can be said that counseling is one of the most effective ways to provide anunderstanding of the legal protection of teachers and students as learners. The legal protection ofteachers among others is legal protection, professional protection and safety protection. Adabstudents in studying among them is a sincere, civilized intentions to people who give knowledge,be patient in studying, write every that is learned, low self-esteem, avoid excessive, adequatesleep, and reduce the word that is not useful.